MONOPOLY OF HAJJ PILGRIM TRANSPORTATION BY THE GOVERNMENT - Bq. Raehanun Ratnasari (Fakultas Hukum Universitas Mataram, 2013)
Implementation of the Hajj is regulated in Law No. 13 of 2008 concerning the organization of the pilgrimage. This law provide legal certainty for the citizens of the State of Indonesia (WNI) who wish to perform the pilgrimage in the holy land of Mecca with a system setup and management implementation. This monopoly is conducted by the Ministry of Religion is a form of monopoly by law. On Presidential Decree number 70 of 2012 on the procurement of goods or services still relied upon by the religious ministry of the republic of Indonesia in Hajj transportation procurement by the government through a public tender process and the law, socio- legal approach empirical through legislation. There are many factors which become obstacle in the implementation of the transport Hajj like structure where the lack of specialized agencies authorized to manage funds Hajj , the substance is not harmony factor . The lack of knowledge about the pilgrims in the field of aviation technology that can interfere with the process of implementation transportation pilgrims. Implementation of transport Hajj performed by the government based on a presidential regulation on procurement of goods and services through a public tender process, but in terms of implementation remain guided in Law No. 13 of 2008 concerning the organization of the HajjKeywords : Monopoly, Transportation, Pilgrimage